Phatic Language in a Specific Culture Perspective in the Context of Internationalization of the Indonesian Language - Rahardi, R K (KnE Social Sciences, 2018)
The main purpose of this study was to describe the form and meaning of phatic language from the perspective of a specific culture in the scope of language internationalization. The source of the data of this study was the speeches of the society in various domains that contained manifestations of phatic language. The data were collected by employing the listening method and the speaking method according to the categories. Data analysis applied the contextual method and the distributional method. The outcomes of this phatic language study from the perspective of a specific culture will be useful for the following: (1) enriching the pragmatic knowledge that still needs to be increased in this country; (2) documenting the sociocultural richness of Indonesian society; (3) supporting the government’s efforts to internationalize the Indonesian language. Keywords: dignified language, Indonesian language internationalization, phatic language, specific culture